Speaking Out in Vietnam : Public Political Criticism in a Communist Party-Ruled Nation - Kerkvliet, Benedict J. (Book collections on Project MUSE., 2019)
"Investigates how public political criticism has evolved into a prominent feature of Vietnam's political landscape since the mid 1990s and how state authorities have dealt with it with a combination of responsiveness, toleration, and repression"--